The Relationship Between Knowledge Level and Accuracy of Primary Menstrual Pain Self-Medication in Tahfidz Qur'an Islamic Boarding School Students Nurul Huda Joyosuko Metro, Malang - Novia, Maulina; Dela, Dela; H, Sugihantoro; A, Hakim; B, Ma’arif (Formosa Journal of Science and Technology, 2023)
Self-medication is the preferred method for treating minor illnesses based on individual decision. The method used is descriptive analysis. Distributing questionnaires directly to a sample of 85 respondents was used to collect data. This research is a correlational analysis research with a cross-sectional design. Samples were collected using a non-random sampling method with a total sampling method. The research results showed that 93% of respondents had a high level of knowledge, 3% had a medium level, and 4% had a low level. In terms of behavior or acquisition, 88.24% had a good rating, 10.59% had a medium rating, and 1.18% had bad behavior. Spearman's rank correlation analysis produced a calculated r value of 0.537 and a p value of 0.000, indicating a strong and significant positive relationship between knowledge of the adequacy of self-assessment and treatment of primary dysmenorrhea and the feasibility of self-treatment.